Strategies to Improve Innovative Behaviour of Madrasah Tsanawiyah Teachers Through Learning Organization, Personality, and Job - Maskanah; Soewarto Hardhienata; Eka Suhardi (International journal of technology and education research, 2025)
Education requires innovative teachers to improve learning quality, but challenges like limited technology and unsupportive policies persist. A survey in MTs (Islamic junior high schools) in Bogor Regency reveals that many teachers struggle to recognize, generate, promote, and implement innovative ideas. This study offers strategies to enhance teachers’ innovative behavior through strengthening learning organizations, job satisfaction, and IT-based training. A quantitative survey method with path analysis and SITOREM Analysis was used to examine variable relationships and determine strategies for improving teachers’ innovative behavior. Data were collected through questionnaires from 252 certified teachers in private MTs in Bogor Regency, with descriptive and inferential statistical analysis measuring the research variables’ direct and indirect effects. The findings show that Learning Organization, Personality, Job Satisfaction, and Organizational Commitment significantly influence teachers’ Innovative Behaviour. Job satisfaction and organizational commitment act as intervening variables in some relationships, except for organizational commitment, which is ineffective as a mediator between personality and innovative behavior. These results emphasize the importance of a supportive work environment and job satisfaction in fostering teacher innovation.